Data communications, computer networks and open systems - Halsall, Fred (Addison-Wesley, 1997)
Drawing on his twenty years as a researcher and teacher, Fred Halsall presents the complex world of data communications and networks with clarity and thoroughness. An invaluable resource to both the student and the practicing computer professional, this fourth edition of the very successful Data Communications, Computer Networks and Open Systems has been extensively updated to reflect the rapid developments in this field.